2016
DOI: 10.1007/s13277-015-4627-0
|View full text |Cite
|
Sign up to set email alerts
|

miR-204 regulates the EMT by targeting snai1 to suppress the invasion and migration of gastric cancer

Abstract: miR-204 was found to be downregulated in gastric cancer (GC) tissues, and the effect of miR-204 function on gastric cancer remains as a mystery. Therefore, this study was aimed at investigating the potential role of miR-204 involved in GC progression. Tissues collected from 60 gastric cancer patients were selected as the case group, while the matched normal paracancer tissues as controls. miR-204 expression levels in tissues and GC cells were detected using real-time fluorescent quantitative PCR. Luciferase as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…In this study, we examined that miR-204 not only suppressed proliferation but also suppressed migration and invasion of gastric cancer cells. In other studies, Zhang et al, Zhang et al, and Liu et al also documented that miR-204 was a suppressor in gastric cancer, which supported our findings [11, 22, 23]. Therefore, miR-204 played a comprehensive suppressing role in many kinds of human cancers.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, we examined that miR-204 not only suppressed proliferation but also suppressed migration and invasion of gastric cancer cells. In other studies, Zhang et al, Zhang et al, and Liu et al also documented that miR-204 was a suppressor in gastric cancer, which supported our findings [11, 22, 23]. Therefore, miR-204 played a comprehensive suppressing role in many kinds of human cancers.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies showed that miR-204 suppressed gastric cancer through targeting USP47, RAB22A, SIRT1, Snai1, and so forth [11, 22, 23]. Getting together, in miR-204 regulation pathway, USP47, RAB22A, SIRT1, Snai1, and so forth and SOX4 may play an associating role contributing to gastric cancer progressing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A very recent review believes that miR-204 acts as a tumor suppressor via promoting apoptosis, decreasing resistance of cancer cells to chemotherapy, and suppressing the self-renewal of cancer stem cells [32]. Interestingly, several research groups tentatively documented the underlying mechanisms that how miR-204 functions in GC development [15, 24, 31, 33]. For example, Sacconi et al demonstrated that miR-204 targeted B cell lymphoma-2 (Bcl-2) mRNA and increased responsiveness of GC cells to 5-fluorouracil and oxaliplatin treatment, and ectopic expression of Bcl-2 counteracted miR-204 proapoptotic activity [15].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, cell lines MKN-28NM and GC9811 had low metastatic potential to the peritoneum while GC9811-P and MKN-28M had higher metastatic potential [21,22]. Cells were grown in the medium of RPMI-1640 (HyClone, USA) containing 10% FBS (fetal bovine serum, HyClone) at 37 • C atmosphere with 5% CO 2 .…”
Section: Gc Cell Linesmentioning
confidence: 99%